Parental Leave Policies and Family Well-being: A Comparative Analysis of Work-Life Balance Across Nations - Rina Anjani; Dewi Sartika (International Journal of Social Welfare and Family Law, 2024)
This study investigates the impact of parental leave policies on family well-being and work-life balance. By comparing parental leave durations, compensation rates, and eligibility criteria across various countries, the research explores how different policies affect parental mental health, family bonding, and gender equality in the workplace. Findings suggest that comprehensive parental leave policies contribute to stronger family bonds and reduced stress, benefiting both parents and children.